2017
DOI: 10.1002/cam4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hereditary cancer in the general population: development and validation of a screening questionnaire for obtaining the family history of cancer

Abstract: One of the challenges for Latin American countries is to include in their healthcare systems technologies that can be applied to hereditary cancer detection and management. The aim of the study is to create and validate a questionnaire to identify individuals with possible risk for hereditary cancer predisposition syndromes (HCPS), using different strategies in a Cancer Prevention Service in Brazil. The primary screening questionnaire (PSQ) was developed to identify families at‐risk for HCPS. The PSQ was valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 37 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Keeping in line with the above estimates, we could expect approximately 100 cases with a path_MMR variant. Unfortunately, genetic services are still underdeveloped across Latin America, and access to genetic testing and counseling is very limited in the region …”
Section: Genetic Profile For Hereditary Crc: Lynch Syndromementioning
confidence: 99%
“…Keeping in line with the above estimates, we could expect approximately 100 cases with a path_MMR variant. Unfortunately, genetic services are still underdeveloped across Latin America, and access to genetic testing and counseling is very limited in the region …”
Section: Genetic Profile For Hereditary Crc: Lynch Syndromementioning
confidence: 99%
“…Consequently, recent updates of the referral guidelines recommend referral of women with less remarkable family history of cancer (8). Studies that examined older versions of NCCN guidelines for HBOC referral of women from the general population identi ed more women with each update (17,22,23). Our study reveals that the NCCN 2019 guidelines identify 16.7% of women from the general Slovenian population as high risk for HBOC.…”
Section: Discussionmentioning
confidence: 72%
“…The criteria that selected these women as high-risk group were a BRCA1/2 pathogenic variant present in the family, patient or a FDR with two or more primary breast cancers, ovarian cancer, breast cancer before age 45 or male breast cancer, or had a combination of three or more speci c cancers present in the family. These shared criteria may represent the core criteria of the guidelines, identifying the highest risk women, since it has already been suggested that agreement of multiple guidelines might be considered for the selection of women with the highest risk for the pathogenic variant, viewing each guideline as an 'expert' and all guidelines as an 'expert panel' (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first two modalities of invitation provided a very low rate of adhesion (11.4% and 16%, respectively), lower than our rate of acceptance. The highest rate of adherence was reached by the phone call (72.6%), demonstrating the validity for this approach for identifying families at risk for BC . However, the telephone approach needs dedicated personnel, and expensive costs for a large regional screening program.…”
Section: Discussionmentioning
confidence: 90%